Orbital Aging: A Computed Tomography–Based Study of 240 Orbits. Issue 3 (24th June 2022) - Ugradar, Shoaib; Manoukian, Narek; Azhdam, Ariel; Le, Alan; Chen, Jessica; Rootman, Daniel; Goldberg, Robert A.; Lambros, Val
Abstract : Background: Previous studies have attempted to explain age-related changes to the orbit in isolation, often producing conflicting results. The authors used highly accurate imaging software to analyze computed tomographic scans to characterize changes related to age objectively. Methods: In this case-control study, patients seen in an ear, nose, and throat clinic were screened for study entry. Male and female participants were divided into two age groups (20 to 30 years and 60 to 75 years). Primary outcomes included measurement of bony orbital dimensions, volume of soft tissues (muscle and fat volume), and anterior globe position. Three-dimensional reconstructions were created of each orbit allowing these measurements. The generalized estimating equation was used so that both orbits from each patient could be included without any bias. Results: The final sample included 240 orbits from 120 patients. There were 30 patients in each age group. Among female participants, the bony orbital volume ( p < 0.05), fat volume ( p < 0.01), and central width ( p < 0.001) of the bony orbit increased with age. The anterior globe position was significantly greater in older female participants ( p < 0.01). For male participants, the fat volume ( p < 0.0001) and central height ( p < 0.03) increased with age; the lateral rim moved posteriorly with age ( p < 0.007). The anterior globe position was not different between the age groups in male participants ( p = 0.56). Conclusion: The female bony orbit expands with age and is associated with a more anterior position of the globe; the male bony orbital volume remains the same and the lateral rim moves posteriorly.